A wood effort - New Sunday Times, Sumitha Martin (2004)
Universiti Putra Malaysia woodworking academic Dr Jegatheswaran Ratnasingam, in collaboration with German professor Dr Frieder Scholz. scored a first in the global woodworking community recently.